Modular synthetic strategies for dipyrrolopyrazines [data] - Rudolph, Matthias; Kahle, Justin; Mackenroth, Alexandra; Hüßler, Christopher; Römgens, Patrick; Schimanski, Paul; Krämer, Petra; Brückner, Margit; Oeser, Thomas; Rominger, Frank; Hashmi, A. Stephen K. (Universität, 2025)
Herein we describe the synthesis of dipyrrolopyrazines via a tandem-Sonogashira coupling with subsequent direct cyclisation of the resulting bisalkynes. The key precursor, di-tert-butyl (3,6-dichloropyrazine-2,5-diyl)dicarbamate, can be easily obtained on a large scale. Bidirectional cross-couplings yield either the diyne or dipyrrolopyrazine scaffolds selectively. When the intermediate bisalkynes are cyclised with IPrAuNTf2, an in situ deprotection of the Boc-group is observed, giving access to the N-unsubstituted dipyrrolopyrazines. Functionalisation of the pyrrolo-CH or NH-moiety allows further adjustment of solubility, processability and optoelectronic properties. Photophysical studies demonstrate remarkable stability and high quantum yields.